Microbiology of Incisional Surgical Site Infection - Majumder, Krisna Rani; Mubin, Samia; Siddique, Md Ibrahim; Elahi, M Nur E (Journal of Surgical Sciences, 2019)
Background: Bacteria responsible for causing lncisional Surgical Site Infection (ISSI) along with their resistance pattern changes over time due to various factors and are a matter of regular scrutiny. Proper understanding of this will help both surgeon and microbiologist to formulate an effective guideline to combat overall SSI. Objectives: To evaluate responsible microorganisms and their resistance pattern causing ISSI following elective gastrointestinal surgery in our perspective. Methods: Prospective data were collected on 1122 surgical patients admitted in the surgery department in BSMMU from January 201 O to June 2012 having elective gastrointestinal surgery. Patients operated were followed in the post operative period till discharge and if any ISSI noted, swab from the site of infection was sent for culture and sensitivity reporting using standard bacteriological techniques. Antibiotics were given accordingly. Results: In this series 1122 wounds were studied of which183(16.31%) cases had ISSI.Wound infection rates, according to clinical wound types were 10.45%, 14.49%, 49% for clean-contaminated,contaminated and dirty wounds respectively. The figures of ISSI according to SSI types were 76.77% for Superficial SSI and 26.23% for Deep SSI.The figures of ISSI according to SSI types were 76.77% for Superficial SSI and 26.23% for Deep SSI. Causative microorganisms were revealed in 74.87% positive cultures. 5.8% wounds had polymicrobial etiology. The common causative organisms were Escherichia coli 55.5%,Staphylococcus aureus 22.6%, Pseudomonas spp. 9.5% and Klebsiella spp. 6.6%.AII were 100% sensitive to Meropenem. Next to this Escherichia coli and Klebsiellaspp. were mostly sensitive to Ceftriaxone 62.5% and 100% respectively, Staphylococcus aureus to Doxicycline 75% and Pseudomonas spp. to Ceftazidime 93.7%. Comparison with previously done national and international studies revealed alarming increase in resistance pattern of causative bacterial isolates. Conclusion: To date no national or in house SSI prevention policy or surveillance guideline exists. Lack of our attention in this issue along with inept, irrational use of antibiotics is definitely adding causative organisms to gain increasing resistance pattern. Before surgical care centers are overwhelmed with SSls by resistant organisms caution must be taken from all level. Journal of Surgical Sciences (2013) Vol. 17 (1) : 18-24